SYSTEMATIC LITERATURE REVIEW: PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK MATA PELAJARAN KIMIA - Rahmadan, Odi; Meilany, Andien Tria; Miterianifa, Miterianifa; Trisnayanti, Yetty (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the effectiveness of the project based learning (PjBL) model in enhancing students' creative thinking skills. Utilizing a qualitative approach through the systematic literature review (SLR) method, the research examines the comparison of existing theories using previous research literature. The data collection process was conducted through systematic searches on electronic platforms mendeley and google scholar, focusing on scientific articles containing in-depth studies about project-based learning models. The literature sources used originated from various published research and academic studies. Systematic analysis results demonstrate that the implementation of the project based learning model has significant potential in developing students' creative thinking abilities. The research conclusion affirms that the project-based learning approach can effectively stimulate and improve students' creative thinking skills.